Guideline for the Management of Fever and Neutropenia in Pediatric Patients With Cancer and Hematopoietic Cell Transplantation Recipients: 2023 Update. Issue 9 (20th March 2023) - Lehrnbecher, Thomas; Robinson, Paula D.; Ammann, Roland A.; Fisher, Brian; Patel, Priya; Phillips, Robert; Beauchemin, Melissa P.; Carlesse, Fabianne; Castagnola, Elio; Davis, Bonnie L.; Elgarten, Caitlin W.; Groll, Andreas H.; et al.
Abstract : PURPOSE: To update a clinical practice guideline (CPG) for the empiric management of fever and neutropenia (FN) in pediatric patients with cancer and hematopoietic cell transplantation recipients. METHODS: The International Pediatric Fever and Neutropenia Guideline Panel reconvened to conduct the second update of this CPG. We updated the previous systematic review to identify new randomized controlled trials (RCTs) evaluating any strategy for the management of FN in pediatric patients. Using the Grading of Recommendations Assessment, Development and Evaluation framework, evidence quality was classified as high, moderate, low, or very low. The panel updated recommendations related to initial management, ongoing management, and empiric antifungal therapy. Changes from the 2017 CPG were articulated, and good practice statements were considered. RESULTS: We identified 10 new RCTs in addition to the 69 RCTs identified in previous FN CPGs to inform the 2023 FN CPG. Changes from the 2017 CPG included two conditional recommendations regarding (1) discontinuation of empiric antibacterial therapy in clinically well and afebrile patients with low-risk FN if blood cultures remain negative at 48 hours despite no evidence of marrow recovery and (2) pre-emptive antifungal therapy for invasive fungal disease in high-risk patients not receiving antimold prophylaxis. The panel created a good practice statement to initiate FN CPG-consistent empiric antibacterial therapy as soon as possible in clinically unstable febrile patients. CONCLUSION: The updated FN CPG incorporates important modifications on the basis of recently published trials. Future work should focus on addressing knowledge gaps, improving CPG implementation, and measuring the impact of CPG-consistent care.